# Use substitution to solve 3x + 2y = 8 and 8x + 3y = -1

### 1 Answer | Add Yours

The system of linear equations:

3x + 2y = 8 ...(1)

8x + 3y = -1 ...(2)

have to be solved using substitution

3x + 2y = 8

=> x = `(8 - 2y)/3`

Substitute in (2)

`(8*(8 - 2y))/3 + 3y = -1`

=> `64/3 - (16y)/3 + 3y = -1`

=> `(-7y)/3 = -1 - 64/3`

=> `(-7y)/3 = -67/3`

=> `y = 67/7`

x = `(8 - 2y)/3`

=> `(8 - (67*2)/7)/3`

=> `-26/7`

**The solution of the system of linear equations is x = `-26/7` and y = **`67/7`